Beyond Belief : Essays on Religion in a Post-Traditionalist World - Bellah, Robert N. (Robert Neelly), 1927-2013 (Book collections on Project MUSE., 1991)
Beyond Belief collects fifteen celebrated, broadly ranging essays in which Robert Bellah interprets the interplay of religion and society in concrete contexts from Japan to the Middle East to the United States. First published in 1970, Beyond Belief is a classic in the field of sociology of religion.